Bacteria Associated With Phaeocystis globosa and Their Influence on Colony Formation - Xu, Shuaishuai; Wang, Xiaodong; Liu, Jie; Zhou, Fengli; Guo, Kangli; Chen, Songze; Wang, Zhao-hui; Wang, Yan (Frontiers in Microbiology, 2022)
Phaeocystis globosa (P. globosa) is one of the dominant algae during harmful algal blooms (HABs) in coastal regions of Southern China. P. globosa exhibits complex heteromorphic life cycles that could switch between solitary cells and colonies. The ecological success of P. globosa has been attributed to its colony formation, although underlying mechanisms remain unknown. Here, we investigated different bacterial communities associated with P. globosa colonies and their influence on colony formation of two P. globosa strains isolated from coastal waters of Guangxi (GX) and Shantou (ST). Eight operational taxonomic units (OTUs) were observed in ST co-cultures and were identified as biomarkers based on LEfSe analysis, while seven biomarkers were identified in P. globosa GX co-cultures. Bacterial communities associated with the P. globosa GX were more diverse than those of the ST strain. The most dominant phylum in the two co-cultures was Proteobacteria, within which Marinobacter was the most abundant genus in both GX and ST co-cultures. Bacteroidota were only observed in the GX co-cultures and Planctomycetota were only observed in the ST co-cultures. Co-culture experiments revealed that P. globosa colony formation was not influenced by low and medium cell densities of Marinobacter sp. GS7, but was inhibited by high cell densities of Marinobacter sp. GS7. Overall, these results indicated that the associated bacteria are selected by different P. globosa strains, which may affect the colony formation and development of P. globosa.